The Development of Candidate Therapeutics for Transmissible Spongiform Encephalopathies - Zolnierczyk, Katarzyna (2021)
Previous studies have shown that addition of recombinant prion into a cell free prion replication assay – PMCA inhibits the formation of PrPSc. Previously naturally existing versions of ovine prion protein were tested: rARQ, rARR and rVRQ within this assay. Of these, rVRQ was the most potent inhibitor of amplification of different scrapie isolates (IC50 value 120 nM) and bovine BSE (IC50 – 171 nM). The main aim of this study was to produce additional molecular clones for expression of recombinant ovine prion protein where codon 136 had been mutated to code for different amino acids. These rPrPs were tested in dose response experiments in order to investigate whether the change at 136 position in ovine PrP could impact on the ability to inhibit or stop the prion protein misfolding compared to previously tested rVRQ. In order to produce rPrP mutants at codon 136, site-directed mutagenesis was used. All rPrPs were purified by metal affinity chromatography taking advantage of the metal binding properties of PrP molecule. All mutated rPrPs were added to protein misfolding cyclic amplification (PMCA) at different concentration and compared to rVRQ. After amplification, samples were digested with Proteinase K (100 µg/ml) and quantified on immunoblots. The best inhibitors were tested with different ovine scrapie (ARQ/VRQ, VRQ/VRQ, AHQ/VRQ), bovine BSE and ovine BSE isolates (ARQ/ARQ). The results showed that three of the recombinant prion proteins: rRRQ, rKRQ and rPRQ (with arginine, lysine and proline at 136 position, respectively) were found to inhibit the PrPSc misfolding significantly better than naturally occurred rVRQ. The structure of rPrP variants and amino acid substitution at 136 position were analysed and different length peptides containing the valine, arginine, lysine and proline at 136 position were designed. None of these peptides analysed in PMCA gave similar levels of inhibition to the equivalent full length recombinant prion protein response. Moreover, structural analysis showed that introduction of longer amino acids at position 136 did not alter the whole scaffold of prion protein. In addition, the longer side chains for arginine136 and lysine136 or pyrrolidine loop in proline could result in more interatomic bonding in comparison to valine136 and therefore could act to stabilize the whole PrP molecule. Furthermore, the presence of the longer side chains of arginine136 and lysine136 would not predict further structure changes because of the ‘structural’ pocket present on the opposite site of position 136 in ovine PrP. The Rov9 cell line could be persistently infected with processed (heated and sonicated) scrapie brain homogenate SSBP1 (VRQ/VRQ) and SSBP1 derived, NaPTA precipitated PrPSc. In both cases, PrPres was detected in cell lysates from induced with 1 µg/ml doxycycline and when 500 µg of total protein was digested with 20 µg/ml of PK followed by PrPres concentration by centrifugation. The best inhibitory rPrPs were used in experiments to prevent the infection with SSBP1 isolate or reduce the PrPres in persistently infected Rov9 cells. As a result, addition of 250 nM of rRRQ, rKRQ and rPRQ prevented the infection of Rov9 cells at culture passage 1. The rPrP variants showed more promising results than natural rVRQ. In contrast, no significant reduction of PrPres was observed when persistently infected Rov9 cells were treated with 250 nM of either variants or natural rPrPs for 4 days. Overall, this work demonstrated a novel therapeutic approach for prion diseases using recombinant prion proteins. The recombinant protein treatment was effective not only in scrapie model but also among other TSEs and therefore these rPrPs or analogous strategy could be applied as potential human TSE therapeutic.